Option C: [tex]f(x)=2x-3[/tex] is the equation that shifts the function 3 units downward.
Explanation:
The given function is [tex]$f(x)=2 x$[/tex]
Now, we shall shift the function 3 units downward.
To shift the function downwards, we shall subtract a constant from the outside of the function results the function to shift downwards.
The general form to shift the function downwards is given by
[tex]y=f(x)-c[/tex]
Thus, substituting [tex]$f(x)=2 x$[/tex] and [tex]c=3[/tex] in the above expression, we have,
[tex]y=2x-3[/tex]
Thus, the equation can be written as
[tex]f(x)=2x-3[/tex]
Hence, the equation that shifts the function 3 units downward is [tex]f(x)=2x-3[/tex]